The Use of Coconut Fiber Padded Seat in Reducing Vibration and Fatigue of Bus Drivers - Sunarsieh Sunarsieh; Paulina Paulina (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Environmental factors such as vibration can affect work fatigue. The previous research results showed that there was a relation between vibration and fatigue, with the use of ergonomic seats by bus drivers. Then conducting experimental research on making ergonomic seat padding made from coconut fiber to reduce the level of vibration and driver fatigue was investigated. The purpose of this research was to analyze the differences in seating vibrations and the bus driver fatigue who did not use a padding seat and one who used it. Methods: The research design was experimental. The research subjects were 42 bus drivers. The vibration intensity was measured using a vibrometer and work fatigue was measured using a reaction timer, then the data were analyzed by T-test. Results: Based on research results the vibration of bus drivers who did not use seat padding was greater than those who did (p=0.001). Those who used seat padding had lower mean fatigue than drivers who did not use it (p=0.001). Conclusion: Vibration and work fatigue in bus drivers who did not use a padding seat was greater than those who used it and the difference was statistically significant. The use of ergonomic seating for bus drivers was very useful for reducing vibration.